Money Wage Determination Revisited - Eckstein, O. (Review of Economic Studies, 1968)
Journal Article Money Wage Determination Revisited Get access O. Eckstein O. Eckstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 2, April 1968, Pages 133–143, https://doi.org/10.2307/2296543 Published: 01 April 1968